Advances in Digital Television - Xu Mengxia (Tongxin xuebao)
Advanced source（video and audio）coding technologies and advanced digital transmission technologies（modulation/demodulation, error-correction coding and adaptive channel equalization）have been adopted in digital television,bringing to the latter many new eminent characteristics,as well as its promising prospects.A new digital television system is emerging, and it would gradually substitute the existing analogue television system, while inheritting the its technologies.